2017
DOI: 10.1007/s11011-017-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor links obesity and thrombotic cerebrovascular diseases: The roles of PAI-1 and obesity on stroke

Abstract: One of the global socioeconomic phenomena occurred during the last decades is the increased prevalence of obesity, with direct consequence on the risk of developing thrombotic disorders. As the physiological inhibitor of tissue plasminogen activator (tPA) and urokinase plasminogen activator (uPA), plasminogen activator inhibitor-1 (PAI-1) is well known for its role in fibrinolysis. More and more evidences have shown that PAI-1 involves in physiopathologic mechanisms of many diseases and metabolic disorder. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 64 publications
0
29
1
3
Order By: Relevance
“…Ours is the first generation in the 200,000-year history of Homo sapiens where more members of our species are overweight and obese than underweight (Di Cesare et al, 2016). This sudden rise in global obesity prevalence from 105 million individuals in 1975 to 641 million in 2014 (Di Cesare et al, 2016) has coincided with a rise in a plethora of obesity related pathologies including cardiovascular disease (Florido et al, 2017), diabetes mellitus (Al-Goblan, Al-Alfi, & Khan, 2014), cancer (Zheng et al, 2017), stroke (R. Chen, Yan, Liu, Wang, & Wang, 2017), vascular dementia (Ilenia, Daniele, Michele, Enea, & Tayebati, 2017), and Alzheimer's disease (Ilenia et al, 2017). Although obesity is most commonly defined as a body mass index or BMI (body mass divided by the square of the body height) of over 30 kg/m 2 , it is fundamentally characterized by an aberrant and excessive accumulation of adipose tissue due to adipocyte hyperplasia and hypertrophy (Muir et al, 2016).…”
mentioning
confidence: 99%
“…Ours is the first generation in the 200,000-year history of Homo sapiens where more members of our species are overweight and obese than underweight (Di Cesare et al, 2016). This sudden rise in global obesity prevalence from 105 million individuals in 1975 to 641 million in 2014 (Di Cesare et al, 2016) has coincided with a rise in a plethora of obesity related pathologies including cardiovascular disease (Florido et al, 2017), diabetes mellitus (Al-Goblan, Al-Alfi, & Khan, 2014), cancer (Zheng et al, 2017), stroke (R. Chen, Yan, Liu, Wang, & Wang, 2017), vascular dementia (Ilenia, Daniele, Michele, Enea, & Tayebati, 2017), and Alzheimer's disease (Ilenia et al, 2017). Although obesity is most commonly defined as a body mass index or BMI (body mass divided by the square of the body height) of over 30 kg/m 2 , it is fundamentally characterized by an aberrant and excessive accumulation of adipose tissue due to adipocyte hyperplasia and hypertrophy (Muir et al, 2016).…”
mentioning
confidence: 99%
“…The reasons for the discrepancy between the effects of CK and KM on TNF-α induced PAI-1 production in EA.hy926 cells and in mice were not clear. It is reported that LPS stimulates TNF-α production from adipocytes and macrophages and produed TNF-α induces PAI-1expression in endothelial cells [36] [37]. Concentrated Kurozu may decrease plasma PAI-1 level (or PAI-1 production) through only inhibiting TNF-α production of adipocytes and macrophages stimulated by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 deposits in the extracellular matrix facilitate the formation of atherosclerotic plaques, thicken the vascular basement membrane and stiffen the vascular walls, thus promoting the onset and development of vasculopathy and therefore atherosclerosis (35)(36)(37). PAI-1 is considered to be closely associated with vascular disease (38); therefore, it is important to determine the regulatory mechanism of action of PAI-1. The present study identified the relevant factors in AMI in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%